2017
DOI: 10.1016/j.tice.2017.05.002
|View full text |Cite
|
Sign up to set email alerts
|

In vitro extracellular matrix accumulation of nasal and articular chondrocytes for intervertebral disc repair

Abstract: Chondrocyte based regenerative therapies for intervertebral disc repair such as Autologous Disc Cell Transplantation (ADCT, CODON) and allogeneic juvenile chondrocyte implantation (NuQu®, ISTO Technologies) have demonstrated good outcomes in clinical trials. However concerns remain with the supply demand reconciliation and issues surrounding immunoreactivity which exist for allogeneic-type technologies. The use of stem cells is challenging due to high growth factor requirements, regulatory barriers and differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 70 publications
0
27
0
Order By: Relevance
“…This has motivated many researchers into identifying and characterizing alternative cell sources for disc regeneration, which is a key step towards translating therapies into clinical practice . Primary, differentiated cells from other skeletal sites with reduced risk for donor site morbidity, such as articular and nasal cartilage, have been investigated in vitro and in animal models for NP regeneration . While these cell types do exhibit some phenotypic differences to native NP cells, their relative ease of isolation, differentiated state and higher propensity to deposit extracellular matrix may make them attractive alternatives in the future and warrant further consideration and exploration.…”
Section: Optimizing Cell Sources and Delivery Techniquesmentioning
confidence: 99%
“…This has motivated many researchers into identifying and characterizing alternative cell sources for disc regeneration, which is a key step towards translating therapies into clinical practice . Primary, differentiated cells from other skeletal sites with reduced risk for donor site morbidity, such as articular and nasal cartilage, have been investigated in vitro and in animal models for NP regeneration . While these cell types do exhibit some phenotypic differences to native NP cells, their relative ease of isolation, differentiated state and higher propensity to deposit extracellular matrix may make them attractive alternatives in the future and warrant further consideration and exploration.…”
Section: Optimizing Cell Sources and Delivery Techniquesmentioning
confidence: 99%
“…Its main role is to regulate dynamic equilibrium of ECM, including various collagenases and elastases incorporated in the matrix and integrated in the plasma membrane [ 27 ]. The synthesis and decomposition of normal intervertebral disc matrix maintain a balance, and its decomposition is mainly through the generation and activation of catabolic enzymes, including MMPs and a disintegrin and metalloproteinase [ 28 ]. The degradation of the matrix is in equilibrium with the synthesis of the new matrix [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The synthesis and decomposition of normal intervertebral disc matrix maintain a balance, and its decomposition is mainly through the generation and activation of catabolic enzymes, including MMPs and a disintegrin and metalloproteinase [ 28 ]. The degradation of the matrix is in equilibrium with the synthesis of the new matrix [ 28 ]. Bone morphogenetic protein-2 (BMP-2), insulin-like growth factor-1, BMP-7 (also known as osteogenic protein-1), growth differentiation factor 5, and transforming growth factor- β can stimulate the synthesis of matrix [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other differentiated cell types such as articular chondrocytes have also been used in whole disc tissue engineering, but only for the NP region, and similar limitations exist in obtaining these cells with respect to donor site morbidity . Nasal chondrocytes may be a promising alternate cell source for tissue engineering of the NP region, as it has been shown that they maintain their proliferative and matrix production capacity even in a simulated disc‐like microenvironment in vitro …”
Section: Challenges For In Vivo Translation Of An Engineered Discmentioning
confidence: 99%
“…44,47 Nasal chondrocytes may be a promising alternate cell source for tissue engineering of the NP region, as it has been shown that they maintain their proliferative and matrix production capacity even in a simulated disc-like microenvironment in vitro. 96 As an alternative to native disc cells, autologous or allogeneic…”
Section: Cell Sourcesmentioning
confidence: 99%